국제교류 기반의 온라인 서비스러닝에서 대학생의 영어학습 경험: S 여대 사례를 중심으로 - 안미리; Miri Ahn; 박인심; Insim Park (Multimedia-Assisted Language Learning, 2024)
This study analyzed the case of an international exchange-based online service-learning course conducted from the second semester of 2022 to the first semester of 2024, exploring the experiences of S Women's University students supporting Korean language and culture learning for multinational Korean learners at UNSW and Monash University in Australia. The research aimed to qualitatively analyze participants’ motivations, challenges, and the impact on their English learning to suggest improvements for service-learning courses linked to university English classes. Participants' motivations included personal growth, English proficiency improvement, multicultural communication skills development, introducing Korean culture and language, changing perceptions of teaching experiences, and enhancing problem-solving abilities. Students faced difficulties such as communication barriers due to language and cultural differences, challenges in planning unstructured volunteer activities, time zone differences, and varying levels of partner engagement. The study found that the service-learning activities significantly improved students’ confidence in using English, reduced fear of conversing with foreigners, enhanced speaking skills through continuous interaction, increased motivation for English learning, and improved understanding of effective communication elements. In conclusion, online global service-learning proved to be an effective educational method for enhancing learners’ English proficiency and learning motivation through authentic and regular communication experiences.